Shape-simplifying Image Abstraction - Kang, Henry; Lee, Seungyong (Computer graphics forum, 2008)
This paper presents a simple algorithm for producing stylistic ion of a photograph. Based on mean curvature flow in conjunction with shock filter, our method simplifies both shapes and colors simultaneously while preserving important features. In particular, we develop a constrained mean curvature flow, which outperforms the original mean curvature flow in conveying the directionality of features and shape boundaries. The proposed algorithm is iterative and incremental, and therefore the level of ion is intuitively controlled. Optionally, simple user masking can be incorporated into the algorithm to selectively control the ion speed and to protect particular regions. Experimental results show that our method effectively produces highly yet feature‐preserving illustrations from photographs.